An in silico Method to developing an epitope-based peptide vaccination against SARS-CoV-2's Envelope Protein (E) - Intesar, Mohammad Nafees (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.